VARYING CHARACTERISTICS IN SECOND LANGUAGE ACQUISITION - Hamdani Hamdani; Irwandi Irwandi (Adisam Publisher, 2025)
This article aims to discuss the variation of characteristics in second language acquisition. The method used to gather data is a literature review. A literature review is employed to examine textbooks, internet resources, and relevant journals pertaining to the study's topic. The process of Second Language Acquisition (SLA) involves a spectrum of diverse characteristics among learners. This article examines the multitude of individual attributes, encompassing cognitive abilities, motivation, age, and learning styles, that contribute to the complexities within Second Language Acquisition (SLA). By acknowledging and exploring these varying traits, this examination aims to elucidate how these individual differences impact the acquisition and mastery of a second language. Understanding and accommodating these diverse characteristics are pivotal in tailoring effective pedagogical strategies and interventions within the domain of language acquisition. This comprehensive analysis underscores the importance of personalized approaches in SLA, emphasizing that recognizing and adapting to the unique needs of each learner can significantly enhance their language learning journey. By integrating these insights into educational practices, educators can foster more effective and inclusive language learning environments.